2017
DOI: 10.1167/iovs.16-20571
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes in the Optic Nerve Head of Glaucomatous Mice Display a Characteristic Reactive Phenotype

Abstract: PurposeOptic nerve head astrocytes, a subtype of white-matter astrocytes, become reactive early in the course of glaucoma. It was shown recently that in the DBA/2J mouse model of inherited glaucoma optic nerve astrocytes extend new longitudinal processes into the axon bundles before ganglion cell loss becomes apparent. The present study aims at testing whether this behavior of astrocytes is typical of early glaucomatous damage.MethodsMice expressing green fluorescent protein in individual astrocytes were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 62 publications
7
59
0
Order By: Relevance
“…With acute injury (nerve crush), astrocyte processes appear to detach from the edge [ 49 ], but this likely reflects the more severe nature of the injury. Similar to our results in the myelinated nerve, astrocyte remodeling following induced short-term elevations in pressure is most extensive distal from the sclera [ 55 ]. Portions of the optic nerve beyond the sclera itself are unlikely to be impacted directly by elevated IOP, and secondary changes could involve different structural mechanisms.…”
Section: Discussionsupporting
confidence: 89%
“…With acute injury (nerve crush), astrocyte processes appear to detach from the edge [ 49 ], but this likely reflects the more severe nature of the injury. Similar to our results in the myelinated nerve, astrocyte remodeling following induced short-term elevations in pressure is most extensive distal from the sclera [ 55 ]. Portions of the optic nerve beyond the sclera itself are unlikely to be impacted directly by elevated IOP, and secondary changes could involve different structural mechanisms.…”
Section: Discussionsupporting
confidence: 89%
“… 1 Although axonal loss is not present within 3 days in the bead injection model, actin reorganization may represent an initial result of IOP-produced strain. The increase in actin area in R1 could be due to the extension of new fine processes 17 to separate adjoining axons that were swelling, resulting in the increase in individual axonal compartments presented in this study.…”
Section: Discussionmentioning
confidence: 75%
“…Changes in astrocyte morphology in glaucoma models have been reported, primarily through immunolabeling of glial fibrillary acidic protein (GFAP), an intermediate filament component in astrocytes. Thickening and thinning of processes, 15 , 16 development of new processes along the ON axis, 17 and reorganization of filaments 18 have been shown after different time points of axonal insult. Tehrani et al 19 showed reorientation of actin-labelled rat astrocyte processes from a direction transverse to the ON axis to that along the ON axis.…”
mentioning
confidence: 98%
“… 1 It is often considered that mechanical insult within the LC contributes to glaucomatous damage. 1 6 This may involve several paths, such as compression or shearing of the RGC axons potentially affecting axoplasmic transport, 3 , 7 stretch-induced activation of astrocytes, 8 13 or disruption of the vasculature and ischemia. 7 , 11 , 14 , 15 Overall, a larger mechanical insult is thought to translate into a higher likelihood of neural tissue damage.…”
mentioning
confidence: 99%